Influence of Work Experience, Motivation and Competence on Mee Macau Surabaya - Ester Julita Sari Ritonga; Rismawati Sitepu; Nur Hidayat; Marten Zebua; Riyan Sisiawan P. (Journal of Islamic Economics Perspectives, 2021)
The purpose of this study was to determine the effect of work experience, motivation and competence on employee performance at Mee Macau Surabaya. This type of research is quantitative with secondary data. The sample in this study were 40 employees at Mee Macau Surabaya. The sampling technique used a population sample / saturated sample. The method of collecting data using a questionnaire. Data analysis using multiple linear regression analysis. The results showed that there was a significant influence between work experience, motivation and competence on employee performance both partially and simultaneously. And the calculation of F is known that Fcount = 51.784> F table 2.87 with a significance of 0.000 <alpha 0.05. Partially it is known that the variables work experience, motivation and competence have a significant effect on employee performance. After the t test (partial) work experience variable (X1) has t count 2.246> t table 2.02108 and from the motivation variable (x2) t count = 12.342> 2.02108 and from the competency variable (X3) t count = 2.058> t table 2,0218.